Intramyocardially Transplanted Neonatal Cardiomyocytes (NCMs) Show Structural and Electrophysiological Maturation and Integration and Dose-Dependently Stabilize Function of Infarcted Rat Hearts. Issue 1 (January 2017) - Maass, Martina; Krausgrill, Benjamin; Eschrig, Simon; Kaluschke, Tobias; Urban, Katja; Peinkofer, Gabriel; Plenge, Tobias G.; Oeckenpöhler, Simon; Raths, Martin; Ladage, Dennis; Halbach, Marcel; Hescheler, Jürgen; et al.
Cardiac cell replacement therapy is a promising therapy to improve cardiac function in heart failure. Persistence, structural and functional maturation, and integration of transplanted cardiomyocytes into recipients' hearts are crucial for a safe and efficient replacement of lost cells. We studied histology, electrophysiology, and quantity of intramyocardially transplanted rat neonatal cardiomyocytes (NCMs) and performed a detailed functional study with repeated invasive (pressure–volume catheter) and noninvasive (echocardiography) analyses of infarcted female rat hearts including pharmacological stress before and 3 weeks after intramyocardial injection of 5 × 10 6 (low NCM) or 25 × 10 6 (high NCM) syngeneic male NCMs or medium as placebo (Ctrl). Quantitative real-time polymerase chain reaction (PCR) for Y-chromosome confirmed a fivefold higher persisting male cell number in high NCM versus low NCM after 3 weeks. Sharp electrode measurements within viable slices of recipient hearts demonstrated that transplanted NCMs integrate into host myocardium and mature to an almost adult phenotype, which might be facilitated through gap junctions between host myocardium and transplanted NCMs as indicated by connexin43 in histology. Ejection fraction of recipient hearts was severely impaired after ligation of left anterior descending (LAD; pressure–volume catheter: 39.2 ± 3.6%, echocardiography: 39.9 ± 1.4%). Repeated analyses revealed a significant further decline within 3 weeks in Ctrl and a dose-dependent stabilization in cell-treated groups. Consistently, stabilized cardiac function/morphology in cell-treated groups was seen in stroke volume, cardiac output, ventricle length, and wall thickness. Our findings confirm that cardiac cell replacement is a promising therapy for ischemic heart disease since immature cardiomyocytes persist, integrate, and mature after intramyocardial transplantation, and they dose-dependently stabilize cardiac function after myocardial infarction.